A Digest of the Laws of the State of Alabama: Containing all the Statutes of a Public and General Nature, in Force at the Close of the Session of the General Assembly, in January, 1833. To Which are Prefixed, the Declaration of Independence; the Constitution of the United States; the Act to Enable the People of Alabama to Form a Constitution and State Government, &c.; and the Constitution of the State of Alabama. With an Appendix, and a Copious Index Page 201, Fire Hunting § 1 (1822) - (:unkn) unknown (General Publisher, 1822)
Prohibited hunting with fire at night-time. Punishable by a fine of fifty dollars. Only construed to "embrace persons hunting deer with a gun and fire at night."
Keywords: HUNTING REGULATION